Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Let $x=(x_1,x_2)$, the norm is given by $[x]=\sqrt{x_1^2+x_1x_2+x_2^2}$

I need to show the triangle inequality holds.

So $y=(y_1,y_2)$ and from $[x+y]\le[x]+[y]$ I got $$4x_1^2y_1^2-6x_1x_2y_1y_2+4x_2^2y_2^2-x_1^2x_2^2-y_1^2y_2^2\ (\text{this must be bigger than }0)$$ after the long-time boring calculation. Then I got stuck! :(

Is there another way to show the triangle inequality or can we get the inequality from that equation?

share|improve this question
    
thanks for the edit! I can't type those fancy letters... –  Math-Nerd Apr 14 at 10:58
2  
I also changed $y=(y_1+y_2)$ to $y=(y_1,y_2)$, that was a typo, right? –  user2345215 Apr 14 at 11:01

1 Answer 1

up vote 6 down vote accepted

Note that $$[x]=\sqrt{(x_1+{\textstyle\frac{1}{2}}x_2)^2+({\textstyle\frac{\sqrt3}{2}}x_2)^2}\ .$$ If you are permitted to use in your proof the triangle inequality for the standard Euclidean norm, you have $$\sqrt{(u_1+v_1)^2+(u_2+v_2)^2}\le\sqrt{u_1^2+u_2^2}+\sqrt{v_1^2+v_2^2}$$ for any real $u_1,u_2,v_1,v_2$. If you now substitute $$u_1=x_1+{\textstyle\frac{1}{2}}x_2\,,\quad u_2={\textstyle\frac{\sqrt3}{2}}x_2\,,\quad v_1=y_1+{\textstyle\frac{1}{2}}y_2\,,\quad v_2={\textstyle\frac{\sqrt3}{2}}y_2$$ you will get what you want.

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.